2021
DOI: 10.1523/eneuro.0052-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Alcohol Exposure on Action and Outcome-Related Orbitofrontal Cortex Activity

Abstract: Alcohol dependence can result in long-lasting deficits to decision-making and action control. Neurobiological investigations have identified orbitofrontal cortex (OFC) as important for outcome-related contributions to goaldirected actions during decision-making. Prior work has shown that alcohol dependence induces long-lasting changes to OFC function that persist into protracted withdrawal and disrupts goal-directed control over actions. However, it is unclear whether these changes in function alter representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…This result aligned with prior findings that raise questions about what behavioral mechanisms control remaining lever presses in goal-directed responding. 33, 42 Thus, broad behavioral performance measures suggested that mice used inferred contingency and expected outcome information to guide their lever press behavior.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This result aligned with prior findings that raise questions about what behavioral mechanisms control remaining lever presses in goal-directed responding. 33, 42 Thus, broad behavioral performance measures suggested that mice used inferred contingency and expected outcome information to guide their lever press behavior.…”
Section: Resultsmentioning
confidence: 99%
“…However, disrupting lOFC activity during every lever press as described above prevented us from determining whether lOFC activity contributed to the encoding of action information, or to the use of prior action information to guide ongoing performance. Another possibility is that inhibiting lOFC during the lever press was akin to enhancing the general reduction in activity normally observed when the animal holds down the lever (Figure 2D), 42 thereby facilitating lOFC processes that could be competing with other action-related processes and associated circuits. Furthermore, inducing interneuron mediated inhibition during every lever press may have recruited compensatory mechanisms for task performance, such that the observed behavioral effects may not be directly attributable to a loss of lOFC function.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations